Stability Indicating Method for the Assay of Remogliflozin Etabonate and its Related Substances by RP-HPLC. Issue 1 (2nd January 2023) - Yadav, Ramji Lal; Dev, Rahul; Santra, Ruchita; Jain, Priti
Abstract: Simple, accurate, precise and stable indicating HPLC methods were developed and validated to determine both related substances and the assay content of Remogliflozin etabonate (RME). The separation was established under optimized chromatographic condition using Waters e2695 HPLC coupled to Ultraviolet detector (UV) at 228 nm with Inertsil ODS-3V C18 column (250 mm x 4.6 mm, 5 μm), injection volume 10 μl for related substances and 20 μl for assay content determination. The mobile phase consisted of 10 mM KH2PO4 buffer with ortho-phosphoric acid pH 2.5. Gradient elution was maintained at a flow rate of 1.0 ml/min using 45°C column oven temperature for determination of the related substances and isocratic elution was maintained at a flow rate of 1.2 ml/min for assay content. The retention time for RME-01, RME-02, RME-03 and RME-04, RME-05 and RME were about 41.74 min, 11.42 min, 20.38 min, 37.16 min, 49.93 min, 25.05 min respectively. The linearity was found to be in the concentration range of 0.312-2.341 μg/ mL for RME-01, 0.306-2.292 μg/ mL for RME-02, 0.306-2.297 μg/ ml for RME-03 and 0.294-2.203 μg/mL for RME-04. The RME was subjected to acid, base, oxidation, and thermal degradation stress conditions. The method was validated according to the ICH guidelines for specificity, precision, linearity, accuracy and robustness and the values were found to be within the limits. GRAPHICAL ABSTRACT: UF0001